2017
DOI: 10.1111/cdev.12854
|View full text |Cite
|
Sign up to set email alerts
|

For Better or Worse? System‐Justifying Beliefs in Sixth‐Grade Predict Trajectories of Self‐Esteem and Behavior Across Early Adolescence

Abstract: Scholars call for more attention to how marginalization influences the development of low-income and racial/ethnic minority youth and emphasize the importance of youth's subjective perceptions of contexts. This study examines how beliefs about the fairness of the American system (system justification) in sixth grade influence trajectories of self-esteem and behavior among 257 early adolescents (average age 11.4) from a diverse, low-income, middle school in an urban southwestern city. System justification was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 62 publications
(101 reference statements)
6
111
3
3
Order By: Relevance
“…People are exposed to multiple system‐justifying ideologies (e.g., the Protestant work ethic, just‐world beliefs, etc.) across the lifespan (Godfrey et al., ; Jost & Hunyady, ). Unless targeted by critical social intervention, adolescents’ endorsement of individual attributions of success is likely to remain stable across adolescence (Aldana & Byrd, ; Freire, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People are exposed to multiple system‐justifying ideologies (e.g., the Protestant work ethic, just‐world beliefs, etc.) across the lifespan (Godfrey et al., ; Jost & Hunyady, ). Unless targeted by critical social intervention, adolescents’ endorsement of individual attributions of success is likely to remain stable across adolescence (Aldana & Byrd, ; Freire, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S., children learn from an early age that success and failure are due to a strong work‐ethic, merit, motivation, and other individual characteristics and behaviors (Jost & Hunyady, ). Although little longitudinal research has examined changes in individual causal attributions for societal disparities, one study with an ethnically diverse sample of early adolescents found that youths’ system‐justification beliefs (i.e., perceptions that society is fair, and thus individuals who fail do so because of a lack of effort or merit) were similar across grades among all groups except for Latino boys (Godfrey, Santos, & Burson, ). Although the assessment of age differences in those beliefs was cross‐sectional, these results nonetheless lend support to the current study's hypothesis that adolescents’ individual attributions would not change over time.…”
Section: Critical Reflection As Individual and Structural Attributionmentioning
confidence: 99%
“…For those who are disadvantaged by the status quo, system justification comes with social and psychological costs. It tends to be negatively associated with self‐esteem, ingroup favouritism, and long‐term psychological well‐being – measured in terms of depression, neuroticism, ambivalence, and stigma internalization (Godfrey, Santos, & Burson, in press; Jost & Thompson, ; Pacilli, Taurino, Jost, & van der Toorn, ). A study of gay men in Chile found that system justification was associated with internalized homonegativity, which was associated with increased symptoms of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Godfrey and colleagues () also found that although system‐justifying beliefs among 257 low‐income and racial/ethnic minority adolescents were positively associated with desirable outcomes in the sixth grade (e.g., higher self‐esteem and better classroom behavior); in older middle school students this relation was reversed. In sum, endorsement of individual blame for being in poverty is common even among those who are living in poverty.…”
Section: Introductionmentioning
confidence: 98%
“…Poverty is a widespread social problem that affects a substantial number of Americans each year. For example, in 2015, 43.1 million people lived below the federal poverty line in the United States (United States Census Bureau, 2016), a figure which vastly underestimates the number of citizens who were unable to meet their basic needs (i.e., earned a living wage; Glasmeier, 2017). Individuals who are living in poverty are at increased risk of experiencing a host of deleterious outcomes, including emotional difficulties, cognitive deficits, educational difficulties, and malnourishment (e.g., Aber, Bennett, Conley, & Li, 1997;Brooks-Gunn & Duncan, 1997).…”
Section: Introductionmentioning
confidence: 99%